2009
DOI: 10.1177/0022466909336752
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Religion and Spirituality in the Special Education Literature

Abstract: Although traditionally not an area of service delivered by special educators, the area of religion and spirituality for persons with disabilities is receiving more attention as a quality-of-life outcome. This literature review examined the special education literature to determine the extent to which special educators are exposed to literature concerned with these issues. The results indicated that information is found in the literature but occurs most often as embedded references in articles on other topics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 67 publications
(88 reference statements)
0
40
0
Order By: Relevance
“…Neither program had collected formal data about the outcomes of their respective programs. Though promising, information from this study and from the literature (Ault, 2010;Carter, 2007) is clearly limited. Future research should include classroom observations as well as interviews with a variety of involved stakeholders, including teachers, administrators, students with disabilities and their families, and peers without disabilities.…”
Section: Next Steps For Researchmentioning
confidence: 72%
See 2 more Smart Citations
“…Neither program had collected formal data about the outcomes of their respective programs. Though promising, information from this study and from the literature (Ault, 2010;Carter, 2007) is clearly limited. Future research should include classroom observations as well as interviews with a variety of involved stakeholders, including teachers, administrators, students with disabilities and their families, and peers without disabilities.…”
Section: Next Steps For Researchmentioning
confidence: 72%
“…Thus, it is important that people with disabilities have equal opportunities to worship, participate, and be educated in their faith. Individuals with disabilities who value religion deserve the necessary support to engage with their faith communities, including in educational settings (Ault, 2010). Hence, the argument about inclusive education is not restricted to Catholic schools particularly, but applies to all faith traditions and to all types of communities associated with them.…”
Section: Rationale For Inclusive Catholic Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Congregations-either on their own, or in partnership with other congregations-can offer a number of critical supports to these families. Indeed, parents and siblings speak often and eloquently of the instrumental role that members of their faith communities have played in their lives (Ault, 2010;Bolduc, 2001). For many of these families, their faith and their relationships within their congregational community can be essential sources of strength and support as they meet the challenges of raising a child with disabilities.…”
Section: Ensuring That Families Flourishmentioning
confidence: 99%
“…Ample evidence supports this assertion (Ault, 2010;Abells, Burbidge, & Minnes, 2008;Orsmond, Krauss, & Seltzer, 2004;Wagner, Cadwallader, Garza, & Cameto, 2003). For example, a 2010 survey by the Kessler Foundation and the National Organization on Disability found that 57% of people without disabilities in the United States said that they attended a church or other place of worship at least once a month.…”
mentioning
confidence: 97%